Strategy formulation for development of leather footwear centre based on capabilities and source of innovation (case study: leather footwear SMEs in Cibaduyut, Bandung) - R Fitriani; M L Singgih; B Syairudin (Institut Teknologi Sepuluh Nopember, 2018)
Small and Medium Enterprises (SMEs) sector is one of an important element in the economic system in Indonesia. This kinds of sector have a major role in developing the employment procurement and the people’s economic condition as well. Thus, it is expected to be well developed and organized. This study aims to identify the strategy used by SMEs based on the influence of SME’s capabilities and source of innovation. This study was conducted by analyzing the influence of variable using structural equation models (SEM) to determine the indicators and variable that have significant influence on SMEs’ capabilities and source of innovation; and classifying the indicator based on SWOT formulation as well. These indicator and variables are categorized into strength-opportunities (SO), strengths-threats (ST), weakness-opportunities (WO), and weakness-threats (WT). The result shows that the weakness-threats (WT) strategy has the most influence value in developing their capabilities and source of innovation. Therefore, the SMEs leather footwear centre in Cibaduyut should focus on the development strategy by considering their weaknesses to confront threats.